"Sounding Brass" and Hellenistic Technology - Harris, William (The Biblical archaeology review, 1982)
No New Testament passage is better known than Chapter 13 of Paul’s first letter to the Corinthians. Its singular lyrical felicity and its insistence upon love differentiates it from the often practical and pragmatic side of Paul’s mind. This ode to love begins (in the King James Version): "If I speak in the tongues […]